Relevansi Pemikiran Ibnu Khaldun Tentang Pendidikan Terhadap Pendidikan Kontemporer - Pitriani, Pipit; Mugni, Subhan; Bachtiar , Machdum (Darajat: Jurnal Pendidikan Agama Islam, 2023)
This study was conducted to describe the relevance of thinking about education as outlined by Ibn Khaldun with contemporary educational theory. This study uses a literature study approach in exploring the relevance of thinking about education as outlined by Ibn Khaldun. In general, the goals of education put forward by Ibn Khaldun contain the principle of balance (tawazun) which means that the goals of education are not only oriented towards happiness in the world but happiness in the hereafter, and education as a result of experience must show changes, especially from human behavior. itself. And changes in students are not only from knowledge, but as a whole both changes in behavior (morals), habits, skills, knowledge, and skills. So that students are able to interact socially well anywhere and with anyone. This is equivalent to the theory of humanistic learning. It is the same with contemporary education that the purpose of education is to achieve the success and happiness of humans in the hereafter, whether it is related vertically to Allah SWT (hablun minallahi), horizontally with humans (hablun minannasi), with nature (hablum minal alam), as well as with oneself. himself (hablun minannafsi). In this case also Abdurrahman Mas'ud has offered the concept of religious humanism, which if realized in the world of Islamic education will be centered on common sense. And the achievements in education must reach three aspects including cognitive, affective, and psychomotor aspects